The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.jnucmat.2020.151984
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-mechanical behavior of Zircaloy-4 claddings under simulated post-DNB conditions

Abstract: The thermo-mechanical behavior of Zircaloy-4 claddings under simulated post-DNB RIA conditions was investigated. Around twenty experiments were performed in simulated post-DNB conditions, i.e. creep ballooning tests with heating rates greater than 1000 • C/s. Two different levels of pressure of 7 and 11 bar were tested for temperatures of interest ranging from 840 • C to 1020 • C. A complex creep behavior was highlighted in this range of temperature. It appears very well correlated to the phase content present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 23 publications
5
20
0
2
Order By: Relevance
“…It is in good agreement with the phase fraction found in the dilatometry experiments. Furthermore, all the results of this study are in good agreement with the creep results of [10] performed in post-DNB conditions.…”
Section: A Kinetic Model Based On Leblond's Equation Was Identifiedsupporting
confidence: 86%
See 2 more Smart Citations
“…It is in good agreement with the phase fraction found in the dilatometry experiments. Furthermore, all the results of this study are in good agreement with the creep results of [10] performed in post-DNB conditions.…”
Section: A Kinetic Model Based On Leblond's Equation Was Identifiedsupporting
confidence: 86%
“…The authors remind that the β fraction is not reliable between 0 and 10% and between 90 and 100%. It can be observed that for all the tests the end of transformation occurs around 960 • C. It is in good agreement with the results of[10]. On the other hand the temperature at which the transformation starts increases with the heating rate.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…The increase, then decrease in creep rate of Zr-2.5%Nb under uniaxial tension, respectively reported between 750 °C and 850 °C, and between 850°C and 950°C, was attributed by Shewfelt et al either to a change in grain size in the two-phase domain [Shewfelt at al 1984], or to a transformation-induced plasticity effect [Shewfelt & Lyall 1985]; nevertheless, no microstructural observations were reported to support the proposed mechanisms. A similar increase in creep rate was reported by [Hunt and Foote 1977, Alymov et al 1987, Fréchinet 2001, Kaddour 2004, Jailin et al 2020] close to the (α+β) / β phase boundary, i.e. in the upper part of the two-phase range, which will be denoted as "near-β" hereafter.…”
Section: Introductionsupporting
confidence: 73%
“…From this, it follows that it is sometimes necessary to work directly on structural samples, in order to take into account the effects of geometry and fabrication process of the specimen on its thermomechanical behavior. On another hand, the loading conditions example, the heating rate may affect the phase transformation of the material [2,3,4] and thus may affect its mechanical properties [3,5,6]. Therefore, the identification of a constitutive model must be done in conditions as close as possible to real life conditions in order to avoid extrapolations that may lead to 30 uncontrolled discrepancies.…”
Section: Introductionmentioning
confidence: 99%